THE EFFECTIVENESS OF ADOBE FLASH-BASED LEARNING MEDIA ON MATHEMATICS LEARNING OUTCOMES - Rusmini; Muhammad Rizky Mazaly; Fitrah Sari Wahyuni Harahap (Jurnal Scientia, 2022)
One of the factors to the lack of success in the mathematics learning process is that the teacher does not innovate in applying the media in learning. In general, teachers at Budi Agung Private High School still apply conventional media so that students become passive and less interested in mathematics. This has an impact to the low student learning outcomes. Therefore, innovation in Adobe Flash-based learning is needed. The purpose of this study was to test the effectiveness of the use of Adobe Flash learning media on students' mathematics learning outcomes at Budi Agung Private High School, Medan. This study uses a quasi-experimental design. Data collection techniques consist of unstructured interviews, observation, documentation, and tests. The data analysis techniques used are the Liliefors test to test the normality of the data, the Levene test to test the homogeneity, the independent sample test, and the party test through one sample t-test to test the hypothesis. The population in this study were classes X-A and X-B SMA Private Budi Agung Medan, totaling 72 students, consisting of 35 students in the experimental class and 37 students in the control class. The results of this study were obtained through the results of the students' final test (post-test). The average post-test result of the experimental class students using Adobe Flash was higher than the control class using conventional methods, with namely the experimental class was 75.1 and the control class was 55.73. And based on the results of the t-test, it was obtained that tcount > ttable, namely tcount = 5.072 and ttable = 1.997 with a significant level of 5% from hypothesis testing Ha was accepted and H0 was rejected, which means that there is an influence on students' mathematics learning outcomes through Adobe Flash-based Learning media